Tadpoles of Central Amazonia (Amphibia: Anura) - Schiesari, Luis; Rossa-Feres, Denise De Cerqueira; Menin, Marcelo; Hödl, Walter (Zootaxa, 2022)
Amazonian lowland rainforests epitomize, as few other biomes, the terrestrial and freshwater biological diversity of our planet. We provide here a comprehensive description of the larval anurans of Central Amazonia, and their natural history. We base our analyses on fieldwork conducted in six terra-firme rainforest and two várzea floodplain sites during ~60 months between 1990 and 2013, complemented with an examination of museum specimens and a review of published literature. Ninety-nine species of anurans are known to occur in Central Amazonia. Of these, 84 species (85%) have a free-swimming exotrophic larva, six species (6%) have a terrestrial endotrophic larva, one species has a terrestrial exotrophic larva (1%) and another seven species (7%) have direct development of eggs into froglets. The life cycle of one species (1%) remains unknown. We formally describe and illustrate the larval stage of 68 species (i.e., 75% of the species with a known larval stage), five of them previously unkown and nineteen never described for Central Amazonia. We compile, review and update information on species natural history including reproductive modes, habitat use, phenology, and species interactions including diet, predators, competitors and parasites. Finally, we assessed the ecomorphological diversity in the region by the application of a system inspired in Altig & Johnston (1989), later updated by Altig & McDiarmid (1999), which recognizes tadpole guilds based on a combination of morphological and natural history data. Basic scientific information presented in this monograph provide the essential background for further studies on the ecological and evolutionary forces shaping anuran Amazonian assemblages, and their conservation.